If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 = 7u + -1 Reorder the terms: 41 = -1 + 7u Solving 41 = -1 + 7u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-7u' to each side of the equation. 41 + -7u = -1 + 7u + -7u Combine like terms: 7u + -7u = 0 41 + -7u = -1 + 0 41 + -7u = -1 Add '-41' to each side of the equation. 41 + -41 + -7u = -1 + -41 Combine like terms: 41 + -41 = 0 0 + -7u = -1 + -41 -7u = -1 + -41 Combine like terms: -1 + -41 = -42 -7u = -42 Divide each side by '-7'. u = 6 Simplifying u = 6
| 2f-5g=-9 | | .25x+5=2 | | 20=5-3p | | 16b-65=9.5 | | i-8=23 | | 300+8p=20 | | -9x-8y=-72 | | t^2-3t-6=5 | | -10(-2x+4)-2(X+1)=-130 | | 0.5(x-12)+2=1.25(x+8)-9.5 | | 8+0.4x=0.9x | | v^2-8v+11=-5 | | 9-8w=-23 | | -4x^4+26x^2-30=0 | | 5(y+4)-7y=10 | | 28=1/2(7)(h) | | (y+2)(y-2)(y^2+4)=0 | | (3x-7)2-5(2x+1)(x-2)=-x-(-(3x+1)) | | m^4-12m^3+36m^2=0 | | 8(8-k)=-2(k-5) | | 3+sqrt(100)=0 | | 6075=c^2 | | 5(q+3k)=4(3k-5q)+q | | 20x-5=1.2 | | 2(p-7)-3p=-12-3p | | 3(n-6)=-5n-2 | | 7x^2-8x=2x^2+4x | | 225+3v=18v | | 6d+2(3+2d)=12 | | 6x^2-16x-70=0 | | 4c^2+17c-15=0 | | 6(1+8v)=6+4v |